Exposure of BALB/c Mice to Diesel Engine Exhaust Origin Secondary Organic Aerosol (DE-SOA) during the Developmental Stages Impairs the Social Behavior in Adult Life of the Males - Win-Shwe, Tin-Tin; Kyi-Tha-Thu, Chaw; Moe, Yadanar; Fujitani, Yuji; Tsukahara, Shinji; Hirano, Seishiro (Frontiers in Neuroscience, 2016)
Secondary organic aerosol (SOA) is a component of particulate matter (PM) 2.5 and formed in the atmosphere by oxidation of volatile organic compounds. Recently, we have reported that inhalation exposure to diesel engine exhaust (DE) originated SOA (DE-SOA) affect novel object recognition ability and impair maternal behavior in adult mice. However, it is not clear whether early life exposure to SOA during the de-velopmental stages affect social behavior in adult life or not. In the present study, to investigate the effects of early life exposure to DE-SOA during the gestational and lactation stages on the social behavior in the adult life, BALB/c mice were exposed to clean air (control), DE, DE-SOA and gas without any particulate matter in the inhala-tion chambers from gestational day 14 to postnatal day 21 for 5 h a day and 5 days per week. Then adult mice were examined for changes in their social behavior at the age of 13 week by a sociability and social novelty preference, social interaction with a juvenile mouse and light-dark transition test, hypothalamic mRNA expression levels of social behavior-related genes, estrogen receptor-alpha and oxytocin receptor as well as of the oxidative stress marker gene, heme oxygenase (HO)-1 by real-time RT-PCR method. In addition, hypothalamic level of neuronal excitatory marker, glutamate was determined by ELISA method. We observed that sociability and social novelty pref-erence as well as social interaction were remarkably impaired, expression levels of es-trogen receptor-alpha, oxytocin receptor mRNAs were significantly decreased, ex-pression levels of HO-1 mRNAs and glutamate levels were significantly increased in adult male mice exposed to DE-SOA compared to the control ones. Findings of this study indicate early life exposure of BALB/c mice to DE-SOA may affect their late-onset hypothalamic expression of social behavior related genes, trigger neurotoxi-city and impair social behavior in the males.